Theoretical and praxeological foundations of investigating crimes against freedom, honor, and dignity in Ukraine during wartime - Філашкін, Вадим Сергійович; Філашкін, В. С.; Filashkin, Vadym S.; Стоянов, Микола Михайлович; Стоянов, М. М.; Stoianov, Mykola M.; Мурзановська, Аліна Владиславівна; Мурзановська, А. В.; Murzanovska, Alina V.; Балобанова, Дар’я Олександрівна; Балобанова, Д. О.; Balobanova, Daria O.; et al. (Florencia : Editorial Primmate S. A. S., 2024)
During armed conflict, human rights violations such as illegal detentions, torture, and enforced disappearances significantly increase, threatening citizens' rights and freedoms. Investigating these crimes in wartime presents unique challenges, including limited access to evidence and the safety risks for victims and witnesses. Effective pre-trial investigations are crucial for justice, restoring victims' rights, and holding perpetrators accountable, which also strengthens public trust in the criminal justice system. This article aims to analyze the theoretical and praxeological foundations of investigating crimes against a person's liberty, honor, and dignity in Ukraine, particularly in wartime. It examines legal norms, procedural aspects, and current challenges in protecting individual rights during conflict, focusing on the difficulties of identifying, investigating, and proving such crimes. The research uses a comparative analysis of Ukraine's legal framework with international standards, empirical research to identify practical challenges, and legal policy analysis to propose improvements. Key findings include the need for specialized investigative practices in wartime, such as remote testimony and alternative evidence collection, and the gap in legal protections during conflict. Recommendations include adopting tailored investigative approaches, strengthening legal safeguards for victims, and providing specialized training for law enforcement to handle wartime crimes effectively. By addressing these issues, Ukraine can improve its criminal justice system in wartime, ensuring justice for victims and maintaining public trust in legal processes even amidst conflict. Під час збройного конфлікту порушення прав людини, такі як незаконні затримання, катування та насильницькі зникнення, значно почастішали, що загрожує правам і свободам громадян. Розслідування цих злочинів у воєнний час представляє унікальні проблеми, включаючи обмежений доступ до доказів і ризики для безпеки жертв і свідків. Ефективне досудове розслідування має вирішальне значення для правосуддя, відновлення прав потерпілих та притягнення винних до відповідальності, що також зміцнює довіру суспільства до системи кримінального правосуддя. Метою статті є аналіз теоретикопраксеологічних засад розслідування злочинів проти свободи, честі та гідності особи в Україні, зокрема у воєнний час. У ньому розглядаються правові норми, процедурні аспекти та поточні проблеми захисту прав особи під час конфлікту, зосереджуючись на труднощах виявлення, розслідування та доказування таких злочинів. Дослідження використовує порівняльний аналіз законодавчої бази України з міжнародними стандартами, емпіричне дослідження для виявлення практичних проблем та аналіз правової політики, щоб запропонувати вдосконалення. Основні висновки включають потребу в спеціалізованих методах розслідування у воєнний час, таких як дистанційне свідчення та альтернативний збір доказів, а також прогалину в правовому захисті під час конфлікту. Рекомендації включають застосування індивідуальних підходів до розслідування, посилення правових гарантій для жертв і забезпечення спеціалізованої підготовки правоохоронних органів для ефективного розгляду злочинів військового часу. Вирішуючи ці проблеми, Україна може покращити свою систему кримінального правосуддя під час війни, забезпечуючи правосуддя для жертв і зберігаючи довіру суспільства до судових процесів навіть під час конфлікту.
Filashkin V. Theoretical and praxeological foundations of investigating crimes against freedom, honor, and dignity in Ukraine during wartime / V. Filashkin, M. Stoianov, A. Murzanovska et al. // Amazonia Investiga. – Florencia : Editorial Primmate S. A. S., 2024. – 13(82). – P. 251–263. Режим доступу: https://hdl.handle.net/11300/32305
Keywords: praxeology; criminal law and procedure; criminalistics; criminal offenses against liberty; honor; and dignity of a person; principles of criminal investigation; праксеологія; кримінальне право та процес; криміналістика; кримінальні правопорушення проти волі; честі та гідності особи; засади розслідування кримінальних правопорушень